1992
DOI: 10.1002/ppul.1950130306
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange during exercise in diabetic children

Abstract: The purpose of this study was to evaluate the cardiorespiratory and metabolic response to exercise in 33 children, aged 9 to 15 years, affected by type I diabetes mellitus, in comparison with 47 age-, sex-, weight-, and height-matched healthy children. All diabetic children were on a mixed split-dose insulin regimen, consisting of both regular and long-acting insulin in the morning and evening. The last insulin injection was administered on average 6 hours before the test. The mean duration of diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Our finding that adolescents with diabetes displayed a 10% reduction in maximal exercise capacity compared with healthy adolescents is consistent with previous studies, which show reductions ranging from 8 to 20% (8,9,12,16). Studies in adults with type 1 or type 2 diabetes have also reported reductions in exercise capacity, but their reductions are usually greater than 20% compared with matched control subjects (1720).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that adolescents with diabetes displayed a 10% reduction in maximal exercise capacity compared with healthy adolescents is consistent with previous studies, which show reductions ranging from 8 to 20% (8,9,12,16). Studies in adults with type 1 or type 2 diabetes have also reported reductions in exercise capacity, but their reductions are usually greater than 20% compared with matched control subjects (1720).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, we cannot be sure this difference in ratios would be maintained as respiratory rates change in vivo, since accurate measurement would be difficult, and the ratio per se would be sensitive to factors beyond respiration, including ATP production, membrane potential, respiratory coupling, and substrate utilization. We do point out that whole body oxygen use is actually increased in insulindeficient diabetes as our data (see text under Animal characteristics) and other reports (1,25,29,31) indicate.…”
Section: Discussionmentioning
confidence: 57%
“…Metabolic issues (such as hyperglycemia and low lactic acid clearance during and after exercise) and respiratory problems (the ventilation reached at peak exercise was lower in proportion to the reduction in O 2 uptake) may relate to reduced anaerobic threshold and early fatigability or loss of performance (12). However, we did not find a difference in V o 2peak max between type 1 diabetic and healthy control athletes.…”
Section: Discussionmentioning
confidence: 99%